Examining Teachers’ and Students’ Perceptions towards the E-Learning Platform at Mohamed Cherif Messaadia University, Souk-Ahras A Case Study of Third Year EFL Students - Sahar BENDJEBBAR (My University, 2024)
Abstract The current study examined both students’ and teachers’ perceptions towards the e-learning platform. The main twofold aims of the undertaken descriptive research work were to examine the views of teachers and students towards the use of the e-learning platform at the level of Mohamed Cherif Messaadia (MCM) University in Souk-Ahras particularly third-year English students. Additionally, it endeavoured to determine the quality of its content and how it is set in comparison with traditional classroom teaching and learning settings. The target population embraced third year students of English language at MCM University, and English language teachers at the same university. The research opted for a mixed methods approach to collect both quantitative and qualitative data. First, a web-based questionnaire was administered to a sample of 37 students selected conveniently from 96 third-year English students. Second, a semi-structured interview was conducted with 05 EFL teachers from the aforesaid university. The findings revealed that students and teachers held positive views towards the e-learning platforms’ usefulness to a certain extent. Besides, both of them faced the same challenging aspects the low-speed internet connection. However, teachers appeared to hold a different view that went in the opposite direction of students in terms of failed online assessments, low engagement, and interaction in addition to limited teacher-student collaboration. --------------------- Résumé La présente étude a examiné les perceptions des élèves et des enseignants à l’égard de la plateforme d’apprentissage en ligne. Les deux principaux objectifs du travail de recherche descriptive entrepris étaient d’examiner les points de vue des enseignants et des étudiants sur l’utilisation de la plate-forme d’apprentissage en ligne au niveau de l’Université Mohamed Cherif Messaadia (MCM) à Souk-Ahras, en particulier les étudiants anglais de troisième année. En outre, elle s’est efforcée de déterminer la qualité de son contenu et la façon dont il est mis en comparaison avec l’enseignement et les contextes d’apprentissage traditionnels en classe. La population cible a accueilli des étudiants de troisième année de langue anglaise à l’Université MCM, et des professeurs d’anglais à la même université. La recherche a opté pour une approche mixte pour collecter des données quantitatives et qualitatives. Tout d’abord, un questionnaire en ligne a été administré à un échantillon de 37 étudiants choisis commodément parmi 96 étudiants de troisième année en anglais. Deuxièmement, un entretien semi-structuré a été mené avec 05 enseignants EFL de l’université susmentionnée. Les résultats ont révélé que les élèves et les enseignants avaient des opinions positives sur l’utilité des plateformes d’apprentissage en ligne dans une certaine mesure. En outre, les deux ont fait face aux mêmes aspects difficiles de la connexion Internet à faible vitesse. Cependant, les enseignants semblaient avoir une opinion différente qui allait dans la direction opposée des élèves en termes d’échecs aux évaluations en ligne, de faible engagement et d’interaction, en plus d’une collaboration limitée entre les enseignants et les élèves. ---------------------- ملخص تعالج الدراسة التي بين أيدينا تصورات كلا من الطلاب والمعلمين تجاه منصة التعلم الإلكتروني. يهدف البحث الوصفي الذي تم القيام به لفحص آراء المعلمين والطلاب تجاه استخدام منصة التعلم الإلكتروني على مستوى جامعة محمد الشريف مساعدية ولاية سوق أهراس. بشكل رئيسي لطلاب السنة الثالثة ليسانس بقسم اللغة الإنجليزية. بالإضافة إلى ذلك، تطرقت الدراسة لتحديد جودة التعلم الإلكتروني مقارنة بالتعليم التقليدي في الفصول الدراسية. اعتمد البحث على نهج الطرق المهجنة لجمع البيانات الكمية والنوعية. أولاً، تم تنفيذ استبيان الكتروني لعينة من 37 طالبًا تم اختيارهم بشكل انتقائي من بين 96 طالبًا من طلاب السنة الثالثة بقسم اللغة الإنجليزية . ثانيا، تم إجراء مقابلة مع 05 مدرسين لغة إنجليزية كلغة أجنبية من الجامعة المذكورة. كشفت النتائج أن كلا الطرفين كانت ليدهم انطباعات إيجابية تجاه منصات التعلم الإلكتروني إلى حد ما. وافق كل منهما إيجابيتها و فائدتها. بالإضافة إلى ذلك، واجه كل منهما نفس التحديات والعوائق؛ أبرزها رداءة شبكة الإنترنت وغياب التعبيرات الوجهية من الطلاب. ومع ذلك بدا أن المعلمين لديهم وجهة نظر مختلفة تسير في الاتجاه المعاكس للطلاب من حيث التقييم عبر الإنترنت، وانخفاض المشاركة والتفاعل بالإضافة إلى محدودية التعاون بين المعلم والطالب